(untitled) (Journal of economic and management development research, 2026)
The accounting treatment of equity transfer under common control is a practical difficulty in enterprise group reorganization. The core dispute lies in the choice between book value method and fair value method. This paper takes the equity transfer transaction within a large group as the research object, focuses on the key basis of commercial substance judgment, and demonstrates that the transaction has sufficient commercial substance from three aspects: strategic intention, cash flow impact, and market-oriented pricing. Based on this, an accounting scheme is constructed in which the transferor recognizes the disposal gain and loss, the transferee handles it hierarchically, and the group level offsets the internal gain and loss. The research shows that fair value measurement can take into account the fairness of legal entity information and the neutrality of group overall information, and form synergy with state-owned assets supervision requirements. This paper provides a reference for the accounting treatment of similar transactions and helps the implementation of the principle.